15 km TBM exploratory tunnel excavation in the construction Lot H33 of the Brenner Base Tunnel. Issue 5 (1st October 2019) - Lussu, Andrea; Grüllich, Sebastian; Kaiser, Christian; Fontana, Adrian
Abstract: The Tulfes Pfons H33 construction contract of the Brenner Base Tunnel includes a 15 km long exploratory tunnel. The tunnel is being driven by an open gripper TBM, permitting a view of the surface of the rock mass, to achieve the best possible geological and geotechnical exploration for the deep tunnel system. Geologists and geotechnical engineers follow the TBM excavation on a daily basis and guarantee ongoing mapping and interpretation of the rock mass classification and of the TBM data. All data from the exploratory tunnel advance, the TBM data, the measured deformations and the seismic explorations as well as the findings of geological mapping are incorporated into the geotechnical longitudinal section, which serves as the basis for the tenders of the main construction contracts. In particular, discussions take place with the designer of the following contract, how the encountered fault zones and overbreaks can be passed successfully in the main tunnels. Both the improvement of the rock mass from the exploratory tunnel and ramps are considered in order to excavate the most difficult fault zones from the exploratory tunnel. Abstract: Das Baulos Tulfes Pfons des Brenner Basistunnel umfasst unter anderem den Bau eines 15 km langen Erkundungsstollens. Der Stollen wird mit einer offen Gripper‐TBM aufgefahren, bei der das Gebirgsgefüge offen einsehbar ist, und soll die bestmögliche geologische und geotechnische Erkundung des tiefliegenden Tunnelsystems ermöglichen. Geologen und Geotechniker verfolgen den TBM‐Vortrieb täglich und garantieren eine Kontinuität bei der Interpretation der Gebirgsparameter und der Maschinendaten. Sämtliche Daten aus den Erkundungsbohrungen, der TBM, den gemessenen Verformungen und den seismischen Untersuchungen sowie die Erkenntnisse aus der Beobachtung des Gebirgsgefüges fließen in den geotechnischen Längenschnitt ein, der als Basis für die Ausschreibungen der Hauptbaulose dient. Besonderes Augenmerk wird dabei auf das Störzonenmanagement gelegt. In Zusammenarbeit mit dem Planer der Folgebaulose wird untersucht, wie diese Störbereiche in den darüber liegenden Haupttunneln erfolgreich durchfahren werden können. Dabei werden sowohl Gebirgsvergütungen vom Erkundungsstollen aus in Betracht gezogen als auch Rampen, um die schwierigsten Störzonen vorab bergmännisch aus dem Erkundungsstollen aus aufzufahren.